Kendali Kecepatan Motor DC Menggunakan DC Chopper Satu Kuadran Berbasis Kontroller PI - Muhamad Ilham Esario; Muldi Yuhendri (Universitas Negeri Padang, 2020)
DC motor is one type of electric motor that is widely used in industry to support the production process. The DC motor speed must be controlled so that it operates in accordance with the desired speed. In this paper, The DC motor control system is proposed using an one quadrant DC chopper based on proportional Integral (PI) controller. The control system is implemented using the arduino mega 2560 microcontroller, which is programmed through Matlab Simulink. Control system devices is also equipped with a keypad for input speed reference and LCD for displaying the speed data. The proposed design in this study was verified through experiments in a laboratory with varying rotor speeds. The experimental results show that the design of a DC motor control system using an one quadran DC chopper based PI controller has worked in accordance with the objectives. This can be seen from the speed response of the motor that operating in accordance with the reference speed inputted via the keypad.